2023
DOI: 10.1038/s42003-022-04407-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide sequencing identifies a thermal-tolerance related synonymous mutation in the mussel, Mytilisepta virgata

Abstract: The roles of synonymous mutations for adapting to stressful thermal environments are of fundamental biological and ecological interests but poorly understood. To study whether synonymous mutations influence thermal adaptation at specific microhabitats, a genome-wide genotype-phenotype association analysis is carried out in the black mussels Mytilisepta virgata. A synonymous mutation of Ubiquitin-specific Peptidase 15 (MvUSP15) is significantly associated with the physiological upper thermal limit. The individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…However, small variations such as point mutations or small indels at one or a modest number of loci can have a large effect. As examples, point mutations have been found that contribute to plant disease resistance 3 , animal heat tolerance 1,2 , and honeybee sensitivity to Varroa mites 4,5 . As another point of reference, as of 2019, half of the pathogenic variants in the human ClinVar database were point-mutations, and almost 90% of clinically relevant insertions and deletions were less than 30bp 54 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, small variations such as point mutations or small indels at one or a modest number of loci can have a large effect. As examples, point mutations have been found that contribute to plant disease resistance 3 , animal heat tolerance 1,2 , and honeybee sensitivity to Varroa mites 4,5 . As another point of reference, as of 2019, half of the pathogenic variants in the human ClinVar database were point-mutations, and almost 90% of clinically relevant insertions and deletions were less than 30bp 54 .…”
Section: Discussionmentioning
confidence: 99%
“…These possibilities are suggested by the growing number of contexts in which one or a modest number of alleles of large effect can produce significant phenotypic benefits for a population. Examples include a single locus that can confer heat resistance in mussels 1 and cattle 2 , fungi resistance in certain plants 3 , or varroa mite resistance in bees 4,5 . There are also collections of loci that have been suggested to contribute to coral resistance to heat 6,7 , bird resistance to malaria 1,8 , or frog resistance to chytrid fungi 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations